Effect of MgO Addition on the Surface and Catalytic Properties of the CuO/AlO System - Nasr-Allah M. Deraz (Adsorption Science & Technology)
The effect of MgO on the solid–solid interactions, surface and catalytic properties of CuO/Al 2 O 3 solids was investigated using XRD methods, nitrogen adsorption at −196°C and oxidation of CO by O 2 at 150–300°C. The nominal composition of the pure mixed solid was 0.20CuO:Al 2 O 3 and the amounts of MgO added varied between 0.43 wt% and 3.30 wt%. The pure and MgO-treated solids were subjected to precalcination (thermal treatment) at 600°C and 800°C, respectively. The results obtained revealed that CuO underwent solid–solid interactions with pure and doped alumina at temperatures of 600°C and above to yield a poorly crystalline copper aluminate (CuAl 2 O 4 ) phase. The amount of copper aluminate produced increased on increasing the precalcination temperature to 800°C. Magnesium oxide inhibited the formation of CuAl 2 O 4 at 600°C but enhanced this reaction at 800°C, the inhibiting and enhancing effects depending on the amount of MgO present. Doping with MgO effected a measurable increase in both the specific surface areas and catalytic activities of the solids precalcined at 600°C. The reverse effect was observed for the doped solids preheated in air at 800°C. Doping at 600°C and 800°C modified the concentration of catalytically active constituents involved in chemisorption and catalysis of the CO oxidation reaction.